Analisis Perbedaan Kinerja Keuangan Rumah Sakit Sebelum dan Sesudah Kebijakan Tanpa Uang Muka - Arifin Arifin; Amal Chalik Sjaaf (Fakultas Kedokteran Universitas Riau, 2018)
The upfront payment policy in the hospital caused controversy and rejection from the society. To anticipate this, some hospitals apply no upfront payment policy. However the policy causes an increase in bad debts. Seeing this dilemma, the authors will conduct research to analyze the different of hospital financial performance before and after no upfront payment policy. The research method used is comparative descriptive with analyzed by paired sample t-test. The result was no upfront payment policy has a positive impact on hospital financial performance. The results of this study were expected to be an input for hospital management and government to revise and refine on the upfront payment policy.